2007
DOI: 10.1111/j.1365-2516.2007.01471.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysing two dinucleotide repeats of FVIII gene in Iranian population

Abstract: Using dinucleotide repeats for carrier detection and prenatal diagnosis of haemophilia A patients, led us to find different alleles and their frequencies in Iranian population. Polymerase chain reaction (PCR) amplification of two short tandem repeat (STR) loci of factor VIII (FVIII) gene was performed, and the PCR products were resolved on 10% native polyacrylamide gel, and samples were analysed with sequenced DNA markers made of PCR cloning of the dinucleotide FVIII gene fragments. Seven different alleles wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
(23 reference statements)
1
3
0
Order By: Relevance
“…The risk of recombination of the external markers limits the use of RFLP in tracking the defective allele. Additional informative intragenic markers, such as STR increase the accuracy of analysis (33). Furthermore, Dai et al (34) observed the HR of 21.57% for G6PD and 35.29% for DXS1108 in Chinese population, which was consistent with previous report (35).…”
Section: Discussionsupporting
confidence: 79%
“…The risk of recombination of the external markers limits the use of RFLP in tracking the defective allele. Additional informative intragenic markers, such as STR increase the accuracy of analysis (33). Furthermore, Dai et al (34) observed the HR of 21.57% for G6PD and 35.29% for DXS1108 in Chinese population, which was consistent with previous report (35).…”
Section: Discussionsupporting
confidence: 79%
“…The polymorphic nature of the STR loci was validated using a comparative genomic approach centred on the interval of interest, essentially as reported for the wide-genome STR map [15]. Briefly, STR sequences in the three human X chromosome reference sequences were aligned using [32], 46 [31], 50 [41], 52 [33], 53 [22], 53 [19], 54 [34] 56 [35], 60 [36], {62-82} à [37], 69 [38], 72 [24], 71 [39], 79 [40], 83 [27], 91 [7] F8Int22 GT 40 [36], 43 [19], 43 [31], 44 [32], 45 [9], 44 [34], 49 [41], 50 [35], {54-70} à [37], 57 [38], 59 [33], 62 [24], 68 [40], 71 [39], 79 [36] Previously reported as F8Int24 [19]; reassigned in this work to the third STR element in Int25 of the F8 gene and recently validated in vitro [20].…”
Section: In Silico Validation Of Polymorphismmentioning
confidence: 99%
“…The risks of recombination of the external markers limit the use of restriction fragment length polymorphisms in tracking the defective allele. Additional informative intragenic markers such as short tandem repeats (STRs) in DNA would thus increase the accuracy of analyses [9].…”
Section: Introductionmentioning
confidence: 99%
“…Additional informative intragenic markers such as short tandem repeats (STRs) in DNA would thus increase the accuracy of analyses [9].…”
Section: Introductionmentioning
confidence: 99%